2004
DOI: 10.1152/jn.00351.2004
|View full text |Cite
|
Sign up to set email alerts
|

Brief Trains of Action Potentials Enhance Pyramidal Neuron Excitability Via Endocannabinoid-Mediated Suppression of Inhibition

Abstract: Fortin, Dale A., Joseph Trettel, and Eric S. Levine. Brief trains of action potentials enhance pyramidal neuron excitability via endocannabinoid-mediated suppression of inhibition. J Neurophysiol 92: 2105-2112, 2004. First published June 2, 2004 10.1152/jn.00351.2004. Depolarization-induced suppression of inhibition (DSI) is a form of retrograde signaling at GABAergic synapses that is initiated by the calcium-and depolarization-dependent release of endocannabinoids from postsynaptic neurons. In the neocortex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 60 publications
6
52
1
Order By: Relevance
“…DSI of CCh-sIPSPs was similarly abolished in WIN-treated cells (data not shown). This confirms previous findings that CCh-sIPSPs are predominantly generated by interneurons with the CB 1 receptor Varma et al, 2001;Fortin et al, 2004), and represents the first evidence that CCK-sIPSPs are generated by interneurons lacking the CB 1 receptor.…”
Section: Cannabinoid Sensitivitysupporting
confidence: 91%
See 1 more Smart Citation
“…DSI of CCh-sIPSPs was similarly abolished in WIN-treated cells (data not shown). This confirms previous findings that CCh-sIPSPs are predominantly generated by interneurons with the CB 1 receptor Varma et al, 2001;Fortin et al, 2004), and represents the first evidence that CCK-sIPSPs are generated by interneurons lacking the CB 1 receptor.…”
Section: Cannabinoid Sensitivitysupporting
confidence: 91%
“…DSI dramatically reduces CCh-sIPSP/Cs (Pitler & Alger, 1992b;Alger et al, 1996;Martin & Alger, 1999;Fortin et al, 2004;Reich et al, 2005) an effect we confirmed in all 18 cells that were tested (e.g., Fig. 3A1).…”
Section: Cannabinoid Sensitivitysupporting
confidence: 72%
“…This view is strengthened by the abundant perisomatic expression of CB 1 Rs in neocortical and PFC interneurons (Tsou et al, 1998;Marsicano and Lutz, 1999). Also, cannabinoids have been shown to increase cortical excitatory transmission and net spiking probability of pyramidal neurons in vivo (Pistis et al, 2001;Fortin et al, 2004), consistent with a concurrent increment of basal glutamate levels and decrement of basal GABA levels in prefrontocortical microdialysis experiments observed in anesthetized (Pistis et al, 2002) and awake (Ferraro et al, 2001) rats, as well as in prefrontocortical in vitro culture (Ferraro et al, 2001;Tomasini et al, 2002).…”
Section: Discussionmentioning
confidence: 66%
“…The action of WIN55,212-2 may be explained by an enhanced feedforward excitatory input along mPFC-DR monosynaptic projections to 5-HT neurons possibly driven by disinhibiting pyramidal neurons (Fortin et al, 2004). Disinhibition was likely engaged by CB 1 R inhibitory control of cortical interneurons (Trettel and Levine, 2002), in agreement with the G i/o -proteinlinked transduction mechanism known to be associated with it and the resultant inhibition of voltage-sensitive calcium channels Figure 6.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, one of the most important challenges is to determine possible physiological modes of DSE-DSI induction. Hence, studies aimed at establishing the physiological patterns of synaptic activity required to induce endocannabinoid release have just started (Brown et al, 2003;Hampson et al, 2003;Fortin et al, 2004;Galante and Diana, 2004). Dopamine (DA) neurons of the ventral tegmental area (VTA) play a central role in motivation, reward-related behaviors, and cognition (Schultz, 2002).…”
Section: Introductionmentioning
confidence: 99%